Want this question answered?
Be notified when an answer is posted
n+n-n-n-n+n-n-n squared to the 934892547857284579275348975297384579th power times 567896578239657824623786587346378 minus 36757544.545278789789375894789572356757583775389=n solve for n! the answer is 42
n2 + n = n(n + 1)
n^2 + n
N+n=0
n = 5
Well, honey, that sequence is all over the place like a drunk driver on a highway. But if we're going by the pattern of adding the number of digits in each number to the end, the next number would be 1113122115. But who knows, maybe the sequence will throw a curveball and give us something completely unexpected.
n n n n n n n n.
n squared x n n x n x n = n cubed n x n = n squared n squared x n = n cubed
The value of the expression n(n-1)(n-2)(n-3)(n-4)(n-5) is the product of n, n-1, n-2, n-3, n-4, and n-5.
N - 5*N = 4*N N - 5*N = 4*N N - 5*N = 4*N N - 5*N = 4*N
(n*n)+n
jazz has been around for a billion years
Barbados \n . Botswana \n . Bulgaria \n . Cameroon \n . Colombia \n . Ethopia \n . Hondurus \n . Kiribati \n . Malaysia \n . Mongolia \n . Pakistan \n . Paraguay \n . Portugal \n . Slovakia \n .
n ,n ,n,n,,n ,,n,n
Assuming you mean the first n counting numbers then: let S{n} be the sum; then: S{n} = 1 + 2 + ... + (n-1) + n As addition is commutative, the sum can be reversed to give: S{n} = n + (n-1) + ... + 2 + 1 Now add the two versions together (term by term), giving: S{n} + S{n} = (1 + n) + (2 + (n-1)) + ... + ((n-1) + 2) + (n + 1) → 2S{n} = (n+1) + (n+1) + ... + (n+1) + (n+1) As there were originally n terms, this is (n+1) added n times, giving: 2S{n} = n(n+1) → S{n} = ½n(n+1) The sum of the first n counting numbers is ½n(n+1).
n+n-n-n-n+n-n-n squared to the 934892547857284579275348975297384579th power times 567896578239657824623786587346378 minus 36757544.545278789789375894789572356757583775389=n solve for n! the answer is 42
The sum of n, n-1, n-2, and n-3 is 4n-6.